If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 7 = x + -1 Reorder the terms: 7 + 8x = x + -1 Reorder the terms: 7 + 8x = -1 + x Solving 7 + 8x = -1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 8x + -1x = -1 + x + -1x Combine like terms: 8x + -1x = 7x 7 + 7x = -1 + x + -1x Combine like terms: x + -1x = 0 7 + 7x = -1 + 0 7 + 7x = -1 Add '-7' to each side of the equation. 7 + -7 + 7x = -1 + -7 Combine like terms: 7 + -7 = 0 0 + 7x = -1 + -7 7x = -1 + -7 Combine like terms: -1 + -7 = -8 7x = -8 Divide each side by '7'. x = -1.142857143 Simplifying x = -1.142857143
| -4(-7+6x)=-236 | | x^2+-20x+39=0 | | d^2+8c+12=0 | | -4+4x=2x+14 | | 6x+6=-2+7x | | 5x^2-22=0 | | 2x-7=7x-32 | | 15.4c-13.7=14x-17.2 | | -4+7X=-2x-94 | | 6x+6=-4x+6 | | 4(3+2x)-7= | | (-21)/3-5*(-5)= | | 4y+16x=20 | | .75(x+2)-(2/3)(x-3)=2 | | 4x-115=95-11x | | 3y=9x-3 | | 6x+10=x+60 | | (2d+1)/3=6 | | 167x+12=1478 | | 3x+7=7x+7 | | -7s-5-7s+9= | | 2y=4x-24 | | x^2-23x+46=0 | | 10y=100x+40 | | -3x+8=-x+32 | | x+5x=48 | | 2X+1=31+7X | | 3x-20=38+5x | | -3+2=23 | | 4+5v+v= | | x^2+16x-82=0 | | 6x-6y=48 |